Proses Kognitif Siswa Dalam Memecahkan Masalah Matematika Melalui Model Problem Based Learning - Mira Fajriati; Badruli Martati; Kunti Dian Ayu Afiani (Journal on Education, 2024)
The research aims to describe students' cognitive processes in solving mathematical problems through a problem based learning model. This research is a descriptive research with a qualitative approach. The research subjects were fourth grade students at MI Muhammadiyah 27 Surabaya. The results of this study indicate that students' cognitive processes in solving mathematical problems through the problem based learning model show certain behaviors at several stages from receiving, processing, storing to recalling information. This behavior is different for each student depending on the abilities they have. This occurs especially at the stage of receiving and processing information.